The development of a cultural family business model of good governance for Greek family businesses in South Africa - Adendorff, Christian Michael (Rhodes University, Faculty of Commerce, Department of Management, 2005)
Never in the history of the South African nation has the entrepreneurial spirit been more alive. Since the opening of international doors, after the 1994 elections, South Africa has experienced the explosive growth of transnational entrepreneurship. An enduring aspect of the explosion of such economic activity is the need for "good governance" and the need for governance education in South Africa and the rest of the continent has never been greater. The size of the family business component of the South Aftican economy suggests that it is the predominant way of doing business in South Africa. Of importance to this study is the estimate that approximately 95 % of all Greek businesses in South Africa can be classified as family businesses. The sustainability of Greek family businesses requires that they maintain good governance practices that are economically and environmentally acceptable to all stakeholders. It also requires that the next generation of Greek entrepreneurs balance good governance for the businesses as well as for the family. The primary objective of this study was to identify and explore the internal factors that influence and determine good governance to ensure the survival, growth and sustainability of Greek family businesses in South Africa. The secondary research objectives pertained to the underlying dimensions of good governance and required an exploration of the different governance concerns in relation to specific South African Greek behaviour and characteristics. A theoretical model of good governance factors was proposed and tested using Structural Equation Modeling. The study found that perceived good governance in a South African Greek family business context needs to be measured in terms of three factors, namely risk control, the internal regulatory environment and the protection of the stakeholders' interest. The study dealt further with the secondary sources effecting governance for South African businesses and was based on the latest report by the King Commission. An important finding is that the cross cultural aspect of family business governance must now be considered when conducting such research as more and more emphasis is placed on the good governance of all businesses.
Keywords: Family-owned business enterprises -- South Africa; Greeks -- South Africa; Greeks -- South Africa -- Social life and customs; Corporate governance -- South Africa; South Africa -- Economic conditions